Breeding objectives and breeding strategies for small ruminants in the tropics. - Kosgey, I.S. (Wageningen University & Research, 2004)
Small ruminants (i.e., sheep and goats) are widespread in the tropics and are important to the subsistence, economic and social livelihoods of a large human population in these areas. The aim of this thesis was to identify the breeding objectives for tropical small ruminants, and to develop appropriate breeding strategies for their improvement. The results indicated that breed substitution and crossbreeding programmes involving temperate breeds are rarely successful due to incompatibility of the genotypes with the farmers' breeding objectives and the production systems. Within-breed selection programmes utilizing indigenous breeds are likely to be more sustainable than breed substitution and crossbreeding. In addition, they help to maintain biodiversity. Indigenous genotypes were predominantly found among pastoral/extensive farmers and mixed crosses among smallholders. In general farmers perceived crosses less favourably than indigenous breeds for a range of traits. The effect was studied of including intangible benefits in the calculation of economic values of breeding goal traits. It resulted in increased values of traits related to longevity. Litter size and lambing frequency were more important traits in smallholder and pastoral production. 12-month live weight also featured prominently in pastoral production. Constraints to small ruminant productivity included low levels of management, disease and parasite challenge, inadequate feed and poor marketing. Nucleus breeding schemes are recommended to optimize the limited available resources. However, 'interactive cycling screening' schemes would be more practical under village settings as the farmers are actively involved in genetic improvement, and minimal recording is required in the commercial flocks. A single nucleus could serve both the smallholder and pastoral production. In conclusion, it is prudent to examine the production system holistically, and involve the producer at every stage in the planning and operation of a breeding programme, integrating traditional knowledge, practices, behaviour and values.